2017
DOI: 10.1111/anae.14029
|View full text |Cite
|
Sign up to set email alerts
|

Nasotracheal intubation over a bougie vs. non‐bougie intubation: a prospective randomised, controlled trial in older children and adults using videolaryngoscopy

Abstract: Conventionally, nasotracheal intubation has consisted of blind nasal passage and external manipulation of the tube through the glottis ('conventional technique'), a technique associated with a high incidence of nasal trauma. We evaluated a novel technique for routine asleep (i.e. post-induction) nasotracheal intubation using a bougie ('bougie technique'), which uses a nasopharyngeal airway to guide a paediatric bougie nasotracheally for use as a Seldinger tracheal intubation guide. Two hundred and fifty-seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…As muscle relaxation facilitates establishing such conditions, the earliest administration of a NMB drug following induction of anaesthesia may well be the most effective management strategy in routine clinical practice. Existing evidence including that provided by the investigation of Solt esz et al [1] [1]. The two techniques described -the conventional and the bougie technique -differ in more than just use of the bougie.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As muscle relaxation facilitates establishing such conditions, the earliest administration of a NMB drug following induction of anaesthesia may well be the most effective management strategy in routine clinical practice. Existing evidence including that provided by the investigation of Solt esz et al [1] [1]. The two techniques described -the conventional and the bougie technique -differ in more than just use of the bougie.…”
mentioning
confidence: 99%
“…The reason for the high bleeding rate in this study is doubtless multifactorial, but the high proportion of 'learners', with little or no experience with the nasal intubation techniques used in the study, would seem to play a significant part. Comparing bougie-guided and conventional nasotracheal intubations using videolaryngoscopya reply I thank Connolly and Ashcroft for their thoughts on our paper [1], which I am grateful for the opportunity to address below.…”
mentioning
confidence: 99%
“…In a randomised controlled trial comparing bougie‐guided and conventional nasotracheal intubation using videolaryngoscopy in older children and adults, Abrons et al. showed that a bougie‐guided technique resulted in significantly less nasal trauma and the need to use Magill forceps compared with a conventional technique, but led to prolonged intubation time and no difference in intubation success rate. To differentiate the effect of one factor on primary study end‐points in a randomised controlled trial, however, all of the other factors have to be standardised for avoidance of potential bias.…”
mentioning
confidence: 99%
“…I thank Connolly and Ashcroft for their thoughts on our paper , which I am grateful for the opportunity to address below.…”
mentioning
confidence: 99%